THE RELATIONSHIP BETWEEN AUTHORITATIVE PARENTING STYLE AND CHILDREN'S EMPATHY AT XAVERIUS 1 KINDERGARTEN JAMBI - Tumewa Pangaribuan; Affan Yusra (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
In the process of forming a child's personality, one form of feeling and thinking that needs to be developed is empathy. The child's empathetic attitude that is directed towards a better direction will be useful in the child's life later, especially when the child is socializing and interacting socially. This study aims to describe the relationship between authoritative parenting style and early childhood empathy. This research is expected to provide benefits for PAUD teachers and parents in an effort to develop children's empathy and shape children's personalities. The parents of Xaverius I Jambi Kindergarten students were used as suggestions to obtain research data. They were given a number of questions to explore their parenting style towards children and to what extent children's empathy can be developed. The data is then processed using quantitative statistical calculations with the product moment correlation formula. Based on the data that has been analyzed, the results show that there is a moderate correlation between authoritative parenting style and empathy for early childhood children at Xaverius I Kindergarten Jambi.Keywords: Authoritative Parenting Style; Early Childhood Empathy. AbstrakDalam proses pembentukan kepribadian anak, salah satu bentuk perasaan dan pemikiran yang perlu di tumbuh kembangkan adalah empati. Sikap empati anak yang diarahkan kearah yang lebih baik akan berguna dalam kehidupan anak nantinya, terutama saat anak bersosialisasi dan berinteraksi sosial. Penelitian ini bertujuan untuk mendeskripsikan hubungan gaya pengasuhan orangtua (parenting style) yang otoritatif dengan empati anak usia dini. Penelitian ini diharapkan dapat memberikan manfaat pada guru PAUD dan orangtua dalam usaha menumbuhkembangkan empati anak dan membentuk kepribadian anak. Para orangtua siswa TK Xaverius I Jambi dijadikan saran untuk mendapatkan data penelitian. Mereka diberikan sejumlah pertanyaan untuk menggali gaya pengasuhan mereka terhadap anak dan sejauh apa empati anak dapat dikembangkan. Data kemudian di olah menggunakan perhitungan statistic kuantitatif dengan rumus korelasi product moment. Berdasarkan data yang sudah dianalisis, diperoleh hasil yang menunjukkan terdapat korelasi sedang hubungan memadai antara gaya pengasuhan (parenting style) orangtua otoritatif dengan empati anak usia dini di TK Xaverius I Jambi.Keywords: Gaya Pengasuhan Orang Tua Otoritatif; Empati Anak Usia Dini.